(untitled) (Teología, 2018)
The article intends to address the perennial newness of the missionary paradigm of the Gospel of Jesus, as stated in Evangelii Nuntiandi and Evangelii Gaudium of Paul VI and Francisco respectively. It will present it in three successive and linked stages. The first on the image of God, indicated in both papal documents: an approach to the Trinitarian-Christological mystery that leads, ô€€€in the other step of the studyô€€€ to the development of the missionary community image of Christ’ disciples (the Church), which will be the responsible of the revelation deposit. In the other step, it addresses the communicability, ô€€€with some of their continuities, developments and challengesô€€€ of the missionary paradigm proclaimed by Jesus and continued by the Church in our time. Finally, it provides some conclusions in the light of the reflections.